Applying exergy analysis for simulation and optimization of the iso-butane recovery process from liquefied petroleum gas - Le, S.N.T. (Italian Association of Chemical Engineering - AIDIC, 2015)
This paper presents the analysis of several distillation process configurations for the recovery of isobutane from a mixture of iso-butane and n-butane from liquefied petroleum gas (LPG), which is produced at Dinh Co GPP in Ba Ria Vung Tau - Vietnam. This project uses the method of process simulations followed by exergy and cost analysis in order to compare the efficiency of energy utilization among the process configuration options. Simulation of a base case and two other distillation process configuration options for separating iso-butane from LPG are implemented via Aspen HYSYS software using Peng-Robinson EOS (equation of state). Exergy is a thermodynamic concept based on the first and second laws to identify process configuration options that use energy inefficiently by locating and quantifying energy wasted through irreversibility or exergy lost. For a base case, the conventional distillation column is simulated with the specified iso-butane product drawn as the side stream. The other process configuration options are a direct sequence distillation and a dividing wall column distillation. The simulation results of the columns are recorded with the purity specifications of about 95 of mass iso-butane in product streams and the recovery ratio of iso-butane exceeding 95 . Then exergy analysis is conducted for each of the three distillation process configurations to find the process configuration in the scope of most efficient energy usage. Unfortunately, the changes in process configuration are accompanied by the adverse effect of capital cost. Therefore a trade-off of energy savings and additional investment expenditure arises. Using a shot-cut cost calculation, it is possible to make the best decision on the distillation process configuration for the recovery of iso-butane from an LPG stream. Copyright Â© 2015, AIDIC Servizi S.r.l.,.